Innovation in the Supply and Procurement of Rig Services - Petter Osmundsen (Center for Economic Studies and ifo Institute (CESifo), 2014)
Substantial elements of innovation have been observable during recent years in rig supply, in particular regarding contracts and organisation. This trend has been driven by the fact that rising costs over many years have put profitability under pressure. On the basis of theory and available empirical insights, the paper outlines the conditions where specific organisational and contractual solutions are best suited. Optimum rig procurement will depend in part on whether the oil companies have time-critical drilling targets, the ability and willingness of the parties to bear risk and the purchaser's competence and capacity to manage and follow up procurement.
Keywords: L60; G34; M10; 330; rig services; contracts; organization; innovation